*SMARTSIM* A multicenter prospective randomized trial of 3D virtual reality versus traditional patient simulation - Erin Donathan; Andrea LaLumia; Charles Foat; Nigel Barr; David I. Page (Journal of the American College of Emergency Physicians Open)
Abstract Objective Simulations are an integral part of paramedic education. Technological advancements have introduced three‐dimensional virtual reality patient simulations (3DVRS), offering a low‐cost, accessible alternative. This study compares the impact of 3DVRS and traditional simulation on paramedic students. Methods Students selected from a convenience sample of 11 cohorts in 10 accredited programs distributed across the United States were allocated to 2 groups using a stratified random sampling. One group received simulations via 3DVRS, the second used traditional in‐person simulation. Students were exposed to 6 scenarios over 2 h from the National Association of Emergency Medical Technicians (NAEMT) Advanced Medical Life Support (AMLS) program. Altered mental status scenarios were selected a priori by the research team containing approximately 30 potential differential diagnoses. A 50‐item posttest was administered using validated cognitive items provided by Fisdap. Results A multicenter prospective randomized trial of 174 paramedic students was undertaken from April until August of 2022. The traditional simulation group was comprised of 88 students and the 3DVRS group had 86 students. A Mann–Whitney U test (U = 4064.5, n1 = 88, n2 = 86, p = 0.396) detected no statistical difference between two distributions or median exam score (70%), the range of values and interquartile range (IQR) for both groups: TS IQR = 64–75 (range, 32–82); 3DVRS IQR = 64–76 (range, 34–86). Conclusion No difference in exam scores using 3DVRS versus traditional simulation was detected. Paramedic programs may have an effective new option when incorporating simulation with 3DVRS, potentially reducing financial and real‐estate resources required with in‐person simulations. Larger studies are needed to truly evaluate the impact and usability of virtual reality on paramedic education.